When Sustainability Disclosure Backfires: ESG, Profitability, and Stock Prices in Indonesian State-Owned Banks - Panjaitan, Raya; Lingga, Gretty R.; Liana, Tri Melda Mei; Octoyuda , Edgar; Silalahi, Andri Dayarana K. (Yayasan Sinergi Kawula Muda, 2026)
This paper examines whether Environmental, Social, and Governance (ESG) disclosure and profitability influence stock prices of Indonesian state-owned banks. ESG reporting has expanded rapidly, yet investor pricing of sustainability information in emerging markets may differ during post-pandemic recovery. Prior studies report mixed evidence and often test ESG or profitability separately, rely on non-bank samples, or overlook the dual-mandate setting of state-owned banks. Beyond an incremental combination of variables, this study advances theory by framing ESG disclosure in state-owned banking as a signal that can reflect both sustainability commitment and perceived policy or cost obligations, while profitability represents a competing fundamental signal; the analysis clarifies how investors weight these signals within the same institutional context. Methodologically, the integrated specification uses quarterly panel variation to estimate sustainability and fundamental effects jointly, improving comparability and reducing omitted-variable concerns relative to single-factor models. Using quarterly panel data for 2022 to 2024, the study covers five state-owned banks, yielding 60 bank-quarter observations; the unit of analysis is the bank and estimation applies random-effects panel regression. ESG is measured using an ESG disclosure score, profitability is proxied by return on assets, and stock price is measured using quarterly closing prices. Results show that ESG disclosure is negatively and significantly associated with stock prices, whereas return on assets is positive but not statistically significant. The findings suggest that stronger disclosure does not automatically translate into higher valuation, underscoring the need for clearer ESG value communication and more comparable, assured reporting.